2002
DOI: 10.1177/194589240201600404
|View full text |Cite
|
Sign up to set email alerts
|

A Diagnostic Dilemma for Chronic Rhinosinusitis: Definition Accuracy and Validity

Abstract: The current symptom-based definition of chronic sinusitis poorly predicts whether a patient truly has chronic sinusitis and needs reevaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 3 publications
5
65
1
3
Order By: Relevance
“…Stankiewicz et al reported poor correlation, while Casiano et al, using a flexible endoscope and Rosbe et al have reported fair to good correlation. [24][25][26] We could not ascertain the scoring system used in these studies. We found a strong correlation between our endoscopy and CT (both Lund-Mackay systems) scores (r = 0.94, p < 0.001).…”
Section: Preoperative Correlationsmentioning
confidence: 95%
“…Stankiewicz et al reported poor correlation, while Casiano et al, using a flexible endoscope and Rosbe et al have reported fair to good correlation. [24][25][26] We could not ascertain the scoring system used in these studies. We found a strong correlation between our endoscopy and CT (both Lund-Mackay systems) scores (r = 0.94, p < 0.001).…”
Section: Preoperative Correlationsmentioning
confidence: 95%
“…Imaging, either by CT scanning or endoscopy, are frequently used as "gold standards," though they give complementary information and are not always in agreement. 6,26 Our questionnaire is unique in that we have chosen to diagnose chronic sinonasal disease rather than to focus specifically on rhinitis and sinusitis, as these diseases represent a continuum, particularly in patients with asthma. Because there is no "gold standard" for the diagnosis of chronic sinonasal disease, we chose to incorporate symptoms, and CT scan and endoscopic findings into our evaluation, and to submit these findings to an expert panel.…”
Section: Discussionmentioning
confidence: 99%
“…CRS Diagnosis Using "Symptoms Alone" The symptom-based component for CRS diagnosis currently emphasizes the 4 cardinal symptoms of nasal obstruction, nasal discharge, facial pain or pressure, and reduction or loss of smell and no longer utilizes minor symptoms (headache, fever, halitosis, fatigue, dental pain, cough, and ear symptoms) because of their frequent absence in CRS and overlap with other medical conditions. 11,655,656,661 Of the cardinal symptoms, prior studies consistently show that discolored nasal discharge and smell loss-individually and especially in combination-enhance the positive predictive value of symptom criteria for CRS diagnosis. 656,660,676,677 Nasal obstruction is almost universal and has the highest average severity among patients with CRS, but its absence in the presence of other cardinal symptoms may be indicative of a non-CRS etiology.…”
Section: Because Of Limited Data Crswnp and Crssnp Are Combined In Tmentioning
confidence: 99%
“…660,661 AR is a hypersensitivity of the nasal mucosa to foreign substances mediated through IgE antibodies. 662 In most cases, sneezing and itching are clues to distinguish AR from CRS, though not in all cases.…”
Section: Viid1 Crssnp Diagnosis: Differential Diagnosismentioning
confidence: 99%